2016
DOI: 10.1099/mic.0.000298
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid biosynthesis during the life cycle of Debaryomyces etchellsii

Abstract: Fatty acid biosynthesis during the life cycle of the ascomycetous yeast Debaryomyces etchellsii cultivated on a non-fermentable substrate, i.e. glycerol, in nitrogen rich media (NRM) and nitrogen limited media (NLM) has been studied. Although considerable activities of key lipogenic enzymes, such as ATP citrate lyase (ACL) and malic enzyme (ME), were detected in vegetative cells during asexual proliferation (which occurred in the first growth stages in both NRM and NLM), lipid accumulation was restricted due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Lipids of both Debaryomyces sp. tested strains presented lower quantities of C18:2 ( ω ‐6) as compared with the relevant studies in which D. etchellsii strain BM1 had been cultivated in shake‐flask nitrogen‐excess and nitrogen‐limited Gly‐based media, where the concentration of C18:2 ( ω ‐6) was always >29·2% w/w of total lipids (Arous et al ).…”
Section: Discussionmentioning
confidence: 79%
“…Lipids of both Debaryomyces sp. tested strains presented lower quantities of C18:2 ( ω ‐6) as compared with the relevant studies in which D. etchellsii strain BM1 had been cultivated in shake‐flask nitrogen‐excess and nitrogen‐limited Gly‐based media, where the concentration of C18:2 ( ω ‐6) was always >29·2% w/w of total lipids (Arous et al ).…”
Section: Discussionmentioning
confidence: 79%
“…Subsequently, citric acid is converted to oxaloacetate and acetyl-CoA (the precursor of FA biosynthesis), through the action of ATP-dependent citrate lyase (ACL). It has been reported that a low or null activity of ICDH and a high activity of ACL in the cytoplasm are key factors for the accumulation of lipids [2,5,6,44,[119][120][121][122][123].…”
Section: Sugar Conversion Into Sco and Regulatory Mechanisms In Sugarmentioning
confidence: 99%
“…Biochemical studies of various enzymes and genes related to lipid biosynthesis have been conducted to understand how oleaginous microbes accumulate lipids under conditions of nitrogen limitation. Key enzymes in lipid biosynthesis, including AMP deaminase (AMPD), ATP-citrate lyase (ACL), malic enzymes (MEs), and acetyl-CoA carboxylase (ACC), cooperate to redirect carbon flux from central carbon metabolism to fatty acid synthesis. Previous studies showed that nitrogen activates AMPD, an enzyme that breaks down cellular AMP, leading to the inhibition of isocitrate dehydrogenase (ICDH). As a result, tricarboxylic acid cycle (TCA cycle) flux is blocked, and accumulated citrate is transported outside the mitochondria and cleaved into acetyl-CoA by ACL, redirecting intracellular carbon to fatty acid synthesis pathways . Therefore, AMPD is a crucial regulator for coping with nitrogen-limited conditions and inducing lipogenesis in oleaginous microbes.…”
Section: Introductionmentioning
confidence: 99%
“…18−20 As a result, tricarboxylic acid cycle (TCA cycle) flux is blocked, and accumulated citrate is transported outside the mitochondria and cleaved into acetyl-CoA by ACL, redirecting intracellular carbon to fatty acid synthesis pathways. 21 Therefore, AMPD is a crucial regulator for coping with nitrogen-limited conditions and inducing lipogenesis in oleaginous microbes. However, its function in the interaction of nitrogen metabolism and lipid synthesis in oleaginous fungi at the molecular level remains unclear.…”
Section: ■ Introductionmentioning
confidence: 99%